Past, present, and intended digitalization around the world: Leading, catching up, forging ahead, and falling behind - Mahsa Samsami; Thomas Schøtt (Naše gospodarstvo / Our Economy, 2022)
Businesses around the world are rapidly adopting digital technologies. Adoption, though, is not even, but it varies over time and differs from society to society, depending on resources in the ecosystem. This study addresses how past, present, and future digitalization is developing globally and, in each society, depending on its resources. A survey of businesses in 47 countries, conducted by the Global Entrepreneurship Monitor in 2021, provides national-level measures of digital technology adoption before and during the pandemic and the intention for adoption in the near future. Adoption of digital technology is found to vary significantly across both time and place. Before the pandemic, adoption was concentrated in the wealthiest societies. The pandemic was an external enabler, pushing less digitalized societies to catch up, independent of national economies, thus entailing some convergence. The early pandemic has been followed by intentions to digitalize, which differ widely, entailing some divergence. Intentions are strong in some societies that are forging ahead, but they are weaker in some less-digitalized and low-income societies that may be falling behind. The findings contribute to understanding digitalization as a global phenomenon and the pandemic as an external enabler that has promoted catching up and convergence in digitalization. Still, ecovery is uneven and entailing divergence, as some societies are forging ahead while others are falling behind.
Keywords: O33; O57; 330; Digitalization; Adoption of technology; External enabler; Globalization; Inequality; Convergence; Divergence